Influence of Salmonella enterica serovar enteritidis infection on the development of the cecum microbiota in newly hatched chicks - Juricova, H; Videnska, P; Lukac, M; Faldynova, M; Babak, V; Havlickova, H; Sisak, F; Rychlik, I (Applied and environmental microbiology, 2013)
Terminal restriction fragment length polymorphism and quantitative PCR showed that the cecal microbiota of chicks up to the age of 21 days was dominated by representatives of the orders Enterobacteriales, Clostridiales, and Lactobacillales. Salmonella enterica serovar Enteritidis infection caused the greatest changes in the gut microbiota when 1-day-old chicks were infected, compared with the infection of 4- and 16-day-old chicks.
Keywords: kur domácí; Cecum; Animals, Newborn; Polymerase Chain Reaction; cékum; polymerázová řetězová reakce; Salmonella enteritidis; Animals; metagenom; Chickens; Metagenome; Salmonella Infections, Animal; zvířata; novorozená zvířata; salmonelová infekce u zvířat